METHODOLOGY OF USING DIFFERENT SOCIAL FORMS IN FOREIGN LANGUAGE CLASSES - Iroda Jakbarova Badriddinʼs daughter (American Journals, 2022)
This article discusses the methodology of using different social forms in foreign language classes, in particular, individual work, pair work, small group work, frontal work, team work.
Keywords: forms of social work, individual work, pair work, work in small groups, frontal work, team work, types of individual tasks, tasks for pair work, tasks for small group work